BUB1B (BUB1 Mitotic Checkpoint Serine/Threonine Kinase B) promotes lung adenocarcinoma by interacting with Zinc Finger Protein ZNF143 and regulating glycolysis. Issue 2 (1st February 2022) - Zhou, Xiaolei; Yuan, Yanli; Kuang, Hongping; Tang, Bingxiang; Zhang, Hui; Zhang, Manlin
ABSTRACT: Lung adenocarcinoma (LUAD) is one of the most common causes of cancer death in men. BUB1B (BUB1 mitotic checkpoint serine/threonine kinase B) has been reported to contribute to the initiation and development of several cancers. Here, we aimed to explore the potential role of BUB1B in LUAD. We found BUB1B was upregulated in LUAD, suggesting its potential role as a biomarker for LUAD diagnosis. Significantly, LUAD patients with high BUB1B expression had a shorter survival time than those with low BUB1B expression. Knocking-out BUB1B resulted in suppression of cell proliferation, migration, and invasion in vitro, and inhibition of tumor growth in the xenograft experiment. Further analysis revealed that BUB1B regulates glycolysis in LUAD and interacting with ZNF143 in LUAD cells. The interaction was demonstrated by silencing ZNF143, which led to a decrease in proliferation, migration, and invasion in LUAD cells, whereas overexpressing BUB1B had the opposite effects. Our study suggested that the ZNF143/BUB1B axis plays a pivotal role in LUAD progression, which might be a potential target for LUAD management. Graphical abstract: uf0001